Using the NN dipole as a theoretical indicator for estimating the electrocatalytic performance of active sites in the nitrogen reduction reaction: single transition metal atoms embedded in two dimensional phthalocyanine. Issue 7 (18th December 2019) - Liu, Fangfang; Song, Luying; Liu, Yunxia; Zheng, Fangfang; Wang, Lu; Palotás, Krisztián; Lin, Haiping; Li, Youyong
Abstract : The dipole of the NN triple bond in an adsorbed N2 molecule as an efficient theoretical indicator for estimating NRR activities. Abstract : The electrocatalytic reduction of nitrogen (N2 ) has recently emerged as an attractive technology for producing ammonia (NH3 ) under mild conditions. Nevertheless, achieving a high selectivity of N2 reduction with respect to hydrogen evolution at relatively low overpotential, and thus increasing the energy efficiency of ammonia production, has remained a key challenge. Herein, with systematic density functional theory (DFT) calculations, we report that the dipole of the NN triple bond in the adsorbed N2 molecule is a more efficient and accurate theoretical indicator compared with the previous ones for predicting the catalytic performance of active sites in the nitrogen reduction reaction (NRR). By screening single transition metal atoms anchored on two-dimensional phthalocyanine (2D Pc) organic frameworks, we show that 2D Mo-Pc is a promising single-atom-catalyst in the NRR with an extremely low onset potential of −0.25 V. The origin of such high catalytic activity can be interpreted by the large dipole moment introduced into the NN bond via strong Mo–N interactions. As a result, the injection of electrons into the anti-bonding orbitals of nitrogen molecules is promoted. In addition, the competing hydrogen evolution reaction (HER) can be effectively inhibited due to the unfavourable bonding interactions between the H and the single Mo atom.